Development of apples as functional food and raw material for the food and beverage industry - Soesilowati, Etty; Mutiara, Titi; Widiyanti; Wijayanti, Febry; Turgel, Iriana Dmitrievna (Journal of Food Technology Research, 2026)
Apples are a source of antioxidants, vitamins, and essential minerals for humans. They have high phenolic content and potential as an anti-diabetic agent. Indonesia ranks fifth globally in the number of diabetes mellitus (DM) sufferers, with 19.5 million cases. This number is projected to increase to 28.6 million by 2045 if no intervention occurs. The objectives of this study are: (1) to utilize apple products in an "apple dip" beverage; (2) to test the bioactive compound activity of the apple dip product; and (3) to assess the feasibility of the business. The urgency of this research lies in: (1) increasing the added value of apple products and farmers’ income; and (2) reducing the prevalence of diabetes in Indonesia. Antioxidant activity was tested using the DPPH method, expressed as the IC50 concentration. Additionally, total flavonoid and phenolic contents were analyzed. Economic aspects were evaluated using Net Present Value (NPV), Benefit-Cost (B/C) ratio, Internal Rate of Return (IRR), and Payback Period. The research results indicated that apples have an IC50 value of 30.25 ppm, classified as strong antioxidant activity. The total flavonoid content was 37.20 mg QE/g, and phenolic content reached 258.94 mg GAE/g. The feasibility analysis showed a Net Present Value of Rp647,177,295.08, indicating the present value exceeds the initial investment. The Benefit-Cost Ratio was 8.3, the Internal Rate of Return was 179%, and the Payback Period was 2 years.